The music of Peter Maxwell Davies - Jones, Nicholas 1973-; McGregor, Richard 1953- (Boydell & Brewer, 2020)
Peter Maxwell Davies (1934-2016) was one of the leading international composers of the post-war period as well as one of the most productive